Sexual dysfunction and associated factors among exclusively breastfeeding Malaysian women - Jamani, Nurjasmine Aida (2020)
Female sexual dysfunction (FSD)defined as distress caused by the unwanted presence or absence of sexual desire, sexual arousal, orgasm and/or associated sexual pain disorder. FSD has a high prevalence regardless of age. Hypoestrogenism and hyperprolactaemia is postulated to cause FSD during breastfeeding